2020
DOI: 10.2147/jmdh.s259905
|View full text |Cite
|
Sign up to set email alerts
|

<p>Anxiety and Its Association with Preparation for Future Specialty: A Cross-Sectional Study Among Medical Students, Saudi Arabia</p>

Abstract: Background: Anxiety disorders are a significant global health concern with destructive morbidity and mortality. Medical school is a stressful environment worldwide. This study measures the prevalence of anxiety symptoms among clinical-year medical students in Saudi Arabia. As well as to explore its association with students' sociodemographic factors, academic performance, issues experienced by them during the study of medicine, and their perceived readiness for their future specialties. Methods: The generalize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 22 publications
2
13
0
1
Order By: Relevance
“…This may be explained by the fact that medical school environments are highly competitive; students are working hard to achieve higher grades and GPA to look for opportunities in the postgraduate residency programs and jobs. These stressors make medical students vulnerable to mental health problems [ 45 ]. Moreover, the presence of students with low GPA or previous failure with their high achieving colleagues could be another burden on them.…”
Section: Discussionmentioning
confidence: 99%
“…This may be explained by the fact that medical school environments are highly competitive; students are working hard to achieve higher grades and GPA to look for opportunities in the postgraduate residency programs and jobs. These stressors make medical students vulnerable to mental health problems [ 45 ]. Moreover, the presence of students with low GPA or previous failure with their high achieving colleagues could be another burden on them.…”
Section: Discussionmentioning
confidence: 99%
“…The reliability, validity, and diagnostic capability of the GAD-7 have been confirmed, but the majority of previous psychometric studies focused on clinical settings rather than general populations (12,23,(27)(28)(29). Although the GAD-7 has been widely used for anxiety screening among medical students (30)(31)(32), few studies have systematically evaluated its measurement properties in this sample. Besides, previous studies have focused on the psychometric performance of the overall scale, but little attention has been paid to the characteristics or measurement invariance of individual items.…”
Section: Introductionmentioning
confidence: 99%
“…Using the World Bank Classification, students were recruited from a mix of high income ( n =39), upper middle income ( n =29), and lower middle income ( n =22) countries, with only two studies conducted in low income countries [ 82 , 120 ]. The majority of included studies were conducted in Asia ( n =34) and the Middle East ( n =21): nine were in Pakistan [ 49 , 51 , 53 , 54 , 86 , 98 , 101 , 104 , 115 ], seven in Saudi Arabia [ 41 , 45 , 46 , 48 , 58 , 80 , 85 ], seven in the People's Republic of China [ 62 , 78 , 84 , 88 , 112 , 124 , 127 ] and five in Egypt [ 42 , 43 , 70 , 73 , 106 ].…”
Section: Resultsmentioning
confidence: 99%
“…Likewise, 19 studies (out of 36) found that females were more likely than males to screen above the cut-off for anxiety [ 11 , 42 , 43 , 48 , 49 , 53 , 57 , 80 , 82 , 90 , 91 , 97 , 100 , 106 , 113 , 116 , 121 , 126 ].…”
Section: Resultsmentioning
confidence: 99%